(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
The inscription engraved in a paleo-Hispanic writing system on a hand-shaped bronze sheet found at the Irulegi site (Valle de Aranguren, Navarra) is an exceptional document. Its finding context (the threshold of a house), its morphology and decoration, the use of a special variant of a paleohispanic writing system, the appearance of some terms as sorioneku/-ke or eŕaukon, which could hypothetically be related to Basque words, and the language used invite us to interpret it as an epigraph of character ritual or religious, perhaps an apotropaic dedication. This paper discusses the aspects in which the piece introduces significant novelties and the most plausible hypotheses for its understanding are proposed.